2013
DOI: 10.1111/vde.12048
|View full text |Cite
|
Sign up to set email alerts
|

In vitro comparison of the effectiveness of polihexanide and chlorhexidine against canine isolates of Staphylococcus pseudintermedius, Pseudomonas aeruginosa and Malassezia pachydermatis

Abstract: The results indicate that polihexanide has comparable in vitro antimicrobial efficacy to chlorhexidine and presents a potential alternative agent for skin and wound antisepsis in veterinary medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Household bleach (Clorox bleach; 6.15% of sodium hypochlorite; The Clorox Company, Oakland, CA, USA) from unopened containers was diluted with tap water to a final concentration of 0.05%, which was used as the starting concentration. The in vitro antimicrobial activity of diluted sodium hypochlorite against the bacteria S. pseudintermedius ( n = 10) and P. aeruginosa ( n = 10) and the yeast M. pachydermatis ( n = 10), after 3 and 5 min contact time, was evaluated by broth microdilution following a previously described protocol . Break‐point dilution or the minimal bactericidal concentration (MBC) and minimal fungicidal concentration (MFC) was defined as the highest dilution or lowest concentration required for killing the strain.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…Household bleach (Clorox bleach; 6.15% of sodium hypochlorite; The Clorox Company, Oakland, CA, USA) from unopened containers was diluted with tap water to a final concentration of 0.05%, which was used as the starting concentration. The in vitro antimicrobial activity of diluted sodium hypochlorite against the bacteria S. pseudintermedius ( n = 10) and P. aeruginosa ( n = 10) and the yeast M. pachydermatis ( n = 10), after 3 and 5 min contact time, was evaluated by broth microdilution following a previously described protocol . Break‐point dilution or the minimal bactericidal concentration (MBC) and minimal fungicidal concentration (MFC) was defined as the highest dilution or lowest concentration required for killing the strain.…”
mentioning
confidence: 55%
“…The in vitro antimicrobial activity of diluted sodium hypochlorite against the bacteria S. pseudintermedius (n = 10) and P. aeruginosa (n = 10) and the yeast M. pachydermatis (n = 10), after 3 and 5 min contact time, was evaluated by broth microdilution following a previously described protocol. 3 Break-point dilution or the minimal bactericidal concentration (MBC) and minimal fungicidal concentration (MFC) was defined as the highest dilution or lowest concentration required for killing the strain. The difference in MBC and MFC distribution among different groups (type of microbial organism, exposure time) was assessed by post-ANOVA Newman-Keuls test.…”
mentioning
confidence: 99%
“…39-45 PHMB has been used clinically for the treatment of amoebic keratitis.46 Against filamentous fungi, PHMB has previously only been tested in strains recovered from ocular infections and domestic pets. 47-53 In addition to its use in cosmetics and ocular products, several FDA-approved wound cleansing products are currently marketed featuring PHMB as the primary active ingredient. Given the severe morbidity associated with soft-tissue IFI, the consequences and constraints of currently available conventional therapies, and availability of several FDA approved compounds for topical use, we examined the antifungal activity PHMB and MH against a panel of molds isolated from clinical soft-tissue invasive fungal infections occurring in our facility.…”
Section: Introductionmentioning
confidence: 99%
“…50 Its antimicrobial activity does not appear to be impaired by the presence of blood or albumin and the optimal pH range is between 5 and 6. 52,55 No literature is available on the residual action of PHMB. A recent review article by Fjeld reported that the number of clinical studies on PHMB are small and not necessarily well controlled.…”
Section: -54mentioning
confidence: 99%